Beyond mindfulness: the importance of body compassion in colorectal cancer distress - Zimmaro, Lauren A.; Christie, Aimee J.; Nicklawsky, Andrew; Altman, Jennifer K.; Carson, James W.; Lieu, Christopher H.; Fang, Carolyn Y.; Reese, Jennifer B. (Frontiers in Psychology, 2025)
ObjectivePsychological distress is common among people diagnosed with colorectal cancer (CRC), often stemming from physical changes and challenges associated with the disease and its treatment. Body compassion, a mindfulness-related construct emphasizing acceptance, defusion, and common humanity of the physical body, may offer new perspectives on the link between mindfulness and distress in cancer patients, but this remains unexplored. This study investigated the relationship between mindfulness, body compassion, and distress in individuals with CRC.MethodsFifty-four people diagnosed with CRC completed surveys assessing demographic and medical characteristics [e.g., stage, treatment status, medical comorbidities (SCQ: Self-Administered Comorbidity Questionnaire)], mindfulness (FFMQ-15), body compassion (BCS), and distress (HADS). Relationships were assessed with Holm-corrected Pearson's correlations. Regression models of mindfulness and distress explored a potential mediating effect of body compassion. Interactions between body compassion and disease burden variables (e.g., SCQ) were explored for moderation.ResultsMindfulness and body compassion were moderately correlated (r = 0.62, p < 0.001), with the strongest relationships observed between the subscales of mindful non-judgment and body compassion defusion (r = 0.70, p < 0.05). Greater mindfulness was associated with lower distress (B = −0.39, CI95% [−0.56, −0.16], p < 0.001). This relationship was significantly mediated by body compassion (B = −0.21, CI95% [−0.38, −0.08], p < 0.001), which accounted for 54% of the total effect (p < 0.001). No evidence of moderation was observed.ConclusionsAmong individuals with CRC, body compassion appears to be a key factor within the mindfulness-distress relationship. Future studies are warranted, particularly experimental designs to assess body compassion as a potential mechanism by which mindfulness-based interventions improve distress.